Devoicing or strengthening of long obstruents in Greenlandic - Rischel, Jørgen (Annual Report of the Institute of Phonetics University of Copenhagen, 1986)
It is a characteristic feature of Modern West Greenlandic that long nonnasal consonants are voiceless, whereas these have short voiced counterparts in the case of continuants. Seen in isolation this distribution is suggestive of spontaneous devoicing of long obstruents, but on the basis of evidence from dialects and from old spellings it is suggested that there may be an old "strengthening" process (segmentalization) underlying this modern feature of voicelessness.